Aggregate size effect on the water retention properties of a lime-treated compacted silt during curing - Wang Yejiao; Cui Yu-Jun; Tang Anh Minh; Benahmed Nadia (E3S Web of Conferences, 2016)
The main drying paths of the water retention curves of lime-treated soils were measured. Aggregate size effect on the water retention property was emphasised. Four soil powders with different maximum aggregate sizes (Dmax = 5, 2, 1 and 0.4 mm) were prepared and mixed with 2% quicklime (by weight of dry soil). Samples were prepared by static compaction at dry side of optimum water content (w = 17%) with a dry density of 1.65 Mg/m3. Suction measurement was performed by a dew-point hygrometer at different curing periods (t = 7, 28 and 90 days). The results obtained show that: i) aggregate size effect is insignificant on the water retention curve of untreated soil in the studied suction range (ca 500 kPa ~ 55 MPa); ii) lime treatment gradually improves the soil water retention capacity with the increasing of curing time; iii) aggregate size effect on water retention property of lime-treated soil becomes significant in the suction range from ca 860 kPa to 9 MPa on the long curing term: treated soils prepared with smaller aggregate size (S0.4 and S1) have a higher water retention capacity rather than soils prepared with larger aggregate size (S5).